Towards an Imaginative Friendship: A Dialogue Between the Concept of Dalihan Na Tolu and the Perichoresis of the Trinity for Christians, Muslims, and Parmalim in the Toba Batak Context - Marpaung, Frans Best Soma (STFT Jakarta, Indonesia, 2024)
Religious diversity is central to the Indonesian context. Since the Reformation, Indonesia has been mired in multifaceted crises such as self-determination conflicts (Aceh and Papua), identity politics, religious fundamentalism, terrorism, and social conflicts. One method of conflict resolution is interfaith dialogue. However, interfaith dialogue is insufficient to resolve the disputes. The limitation of this approach is that it disregards the importance of local issues and wisdom. Toba Batak is a tribe in North Sumatra where Christians, Muslims, and Parmalim coexist and live together. Dalihan Na Tolu explains that each human being has one essence in three persons, namely Hula-hula (blessing giver), Dongan Tubu (companion), and Boru (servant). Dalihan Na Tolu brings Christian, Muslim, and Parmalim into a trilogue. This research seeks to engage the concept of Dalihan Na Tolu with the idea of perichoresis of the Trinity, examining how this dialogue can shape a contextual understanding of God and Jesus Christ in the Toba Batak context. The pivotal inquiry pertains to integrating the concepts of Dalihan Na Tolu and perichoresis, fostering an imaginative model for interfaith dialogue within the Toba Batak context. Ultimately, this study proposes a contextual paradigm that promotes a trilogue among Christians, Muslims, and Parmalim, addressing Indonesia's complex tapestry of religious coexistence.